The Influence of Work Motivation, Discipline, and Work Environment on Employee Performance at the Karangturi Village Office, Klaten - Difta Nur Arifin (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This study aims to test whether there is an influence of work motivation, discipline and work environment on the performance of study employees at the Karangturi Village Office, Gantiwarno District, Klaten Regency. The method used in this study is quantitative with a sampling method using a questionnaire. The research sample includes all employees of the Karangturi Village Office, Gnatiwarno District, which is 40 respondents. Data collection was carried out using a questionnaire distribution processed with the SPSS version 25 software application which was used as a data analysis tool. The results of the analysis of this study indicate that work motivation has a negative and insignificant effect on employee performance, discipline has a positive and significant effect on employee performance, while the work environment does not significantly affect employee performance at the Karangturi Village Office, Gantiwarno District, Klaten Regency.